New distribution records of Huperzia wusugongii (Huperziaceae) in West China, with discussions on its nomenclature and related taxa - Yu, Ding-Xiang; He, Hai (Phytotaxa, 2025)
Huperzia wusugongii, a replacement name of H. rubricaulis, was considered as an endemic species known only from a single gathering in northwestern Yunnan. Morphologically similar individuals have been recently found in southwestern Chongqing, southern Sichuan, and southern Yunnan. Molecular-phylogenetic analysis resolved those materials within a group, suggesting that H. wusugongii might have a much broader distribution. However, its taxonomic relationship with the Himalayan species, H. mazumdariana, remains to be tested. Its nomenclatural priority is here discussed under the conspecific hypothesis. Considering its rarity, we studied the associated plants in the Chongqing population and present a detailed list of the accompanying species. Further molecular studies with expanded taxon sampling, including similar species described in Southwest China and neighboring regions, are needed to determine whether these newly documented populations may represent new cryptic endemic species.